Compatibility of NiO/CuO in Ca‐Cu chemical looping for high‐purity H2 production with CO2 capture - Tan, Lili; Qin, Changlei; Zhang, Zhonghui; Ran, Jingyu; Manovic, Vasilije (Wiley, 2018)
Ca‐Cu chemical looping is a novel and promising approach in converting methane into pure H2 following the principle of sorption‐enhanced reforming. Its operational efficiency is largely determined by an appropriate coexistence of Cu‐based oxygen carriers and Ni‐based catalysts. In this work, NiO/CuO composites were synthesized and their catalytic activity for H2 production was measured using a fixed‐bed reactor system equipped with an online gas analyzer. It is reported for the first time that the presence of CuO could hinder the activity of Ni‐based catalysts in H2 production, and experimental results show that the negative effect of CuO is strengthened with increasing CuO content and calcination temperature during sample preparation. With the help of a series of specific test and characterization techniques (SEM‐EDS, BET, XRD, TPR and XPS), interaction rules between NiO and CuO was further investigated and understood, and based on that an action mechanism model was proposed. Furthermore, an arrangement of mixed particles that avoiding the intimate contact of CuO/NiO was suggested and tested, and a superior performance was demonstrated while observing no restrictions of CuO on Ni‐based catalysts in sorption‐enhanced steam‐methane reforming under the conditions of Ca‐Cu chemical looping.
Keywords: Ca-Cu chemical looping; hydrogen production; Ni/Cu interaction; CO2capture